2015
DOI: 10.3109/14767058.2015.1038513
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adopting the IADPSG screening guidelines on the risk profile and outcomes of the gestational diabetes population

Abstract: Objective: To compare characteristics and outcomes of women diagnosed with gestational diabetes mellitus (GDM) by the newer one-step glucose tolerance test and those diagnosed with the traditional two-step method. Research design and methods: This was a retrospective cohort study of women with GDM who delivered in 2010–2011. Data are reported as proportion or median (interquartile range) and were compared using a Chi-square, Fisher's exact or Wilcoxon rank sum test based on data type. Results: Of 235 women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, the patients included in this analysis had consented to be part of a study, and so the findings cannot be extrapolated to unselected patients in usual clinical care. Much of the other previous literature in this area has examined outcomes at single sites before and after the adoption of new criteria . In addition to the lack of generalisability possible in studies from a single centre, all those identified with GDM using either strategy were treated in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patients included in this analysis had consented to be part of a study, and so the findings cannot be extrapolated to unselected patients in usual clinical care. Much of the other previous literature in this area has examined outcomes at single sites before and after the adoption of new criteria . In addition to the lack of generalisability possible in studies from a single centre, all those identified with GDM using either strategy were treated in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the effects of treated GDM on outcomes for women diagnosed by IADPSG criteria versus prior/usual criteria including a modified 75-g CC [ 41 ], NDDG [ 56 ], or a modified two-step WHO 1999 [ 57 ] demonstrated similar pregnancy and neonatal outcomes as those diagnosed by CC and NDDG criteria, but greater risk of macrosomia and LGA compared with WHO criteria. These results suggest that IADPSG criteria may diagnose women with similar risk of adverse outcomes as CC and NDDG, but may identify women at higher risk of adverse outcomes than WHO.…”
Section: Impact Of the Application Of Iadpsg Criteriamentioning
confidence: 99%
“…Women diagnosed with GDM by IADPSG criteria had similar prevalence of risk factors as women diagnosed by CC, NDDG, or WHO criteria. Risk factors studied included South Asian high-risk ethnic group [ 29 ], prepregnancy overweight [ 29 , 41 ], maternal age [ 32 , 41 ], fasting insulin [ 32 ], no regular exercise [ 32 ], and one or more ACOG risk factors [ 56 ].…”
Section: Impact Of the Application Of Iadpsg Criteriamentioning
confidence: 99%
“…The Italian guidelines reserve the execution of the OGTT only to classes of risk, but use the same cutoff values of International Association of Diabetes and Pregnancy Study Groups [11]. The advantage of these new guidelines to identify with more accuracy the pregnant women at the risk of developing DM has been debated, particularly regarding the concern for the medicalization of pregnancy, the treatment costs and the limited evidence of benefits for the treatment at lower diagnostic thresholds resulting in overestimated diagnosis [12]. Lower cutoff might be useful to identify also cases in which an exalted glucose steal mechanism (high glucose flux from pregnant to fetus) could result in a false-negative OGTT.…”
Section: Discussionmentioning
confidence: 99%